(untitled) (Latakia University Journal -Biological Sciences Series, 2024)
The research was conducted in a pot in season 2022-2023 in a green-house at Tishreen University, to investigate the response of four Syrian bread soft wheat (Sham4, Sham6, Sham8, Sham10) to increasing levels of phosphorus fertilization (0, 10, 20, 30, 40 mg P/kg) which correspond to (0, 20, 40, 60, 80, 100 kg P/ha), sowing was in calcareous soil with low phosphorus content with rate of Seeding (9 plants/pot). Some growth and productivity parameters were studied. The increased phosphate fertilizer rates on four cultivars led to significant increase in number of tillers productive, plant height, number grains in spike, thousand grains weight, grain yield, biological yield. Sham8 had a higher number of productive tillers at rate 100 kg P/ha, which reflected positive on grains yield, it was (17.1 ton/ha), Followed by Sham 4 and Sham 6 with close productivity (16.4 - 16.5 tons/ha), respectively. While the lowest productivity was in Sham 10 (14.5 tons/ha), Sham10 had higher biological yield which was 25.3 ton/ha at level 100 kg P/ha, while the biological yield was close in Sham4, Sham6, Sham8 (20.7, 21.5, 20,5 ton/ha), respectively. This distinction for sham10 maybe comes from superiority in plant heights.It distinction by the lowest value of recovery efficiency at rate 100 kg P/ha which was 44.6%, its value decreased with increase in phosphate fertilization rate compared th control that didn’t receive any fertilization. Reaching (56.9%, 55.8%, 52,2%) at the rate 100 kg P/ha in (Sham4, Sham6, Sham8) respectivelyThe productivity on four cultivars was close in number of grains, grain weight, weight of 100 grains